Comparative assessment on learning outcomes achievement among students participating in uniform bodies programs in a Malaysian Public University - Roslee Rajikan,; Siti Nurain Abdul Jalil,; Wu, Suet Kei; Tan, Mei Ting; Ng, Say Theng; Tan, Chian Ying; Noor Fairuzi Suhana Yahya,; Noor Fhadzilah Mokhtar,; Chang, Yin Nee; Norafifah Ahmad Shabri,; Nor Nabilah Abdul Ghani,; Luqmanul Harris Ghani,; et al. (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2017)
Extracurricular activities are extra activities outside the classroom, besides curriculum. It is also known as co-curriculum. University students are encouraged to participate in co-curriculum activities as it can help students improve their soft skills. AIM: A cross sectional survey was conducted to evaluate the achievement of learning outcomes among students who participated in various uniform bodies programs in a Malaysian public university. Furthermore, this research wanted to assess the reasons students participated in the uniform bodies programs and evaluate the effects of such involvement in the extra-curricular in terms of academic performance, time management and social life. The skills that student’s learnt from the extra- curricular were also evaluated. METHOD: A set of validated questionnaire was used as a research tool. The uniform bodies that participated in this survey were ROTU, SUKSIS, BSMM and SISPA. The total number of respondents was 333 students. Statistical Package (SPSS) version 20.0 was used for analysis of data. RESULTS: The study found that majority of students participated in uniform bodies programs because of their own interest the programs (31.5%). There were positive correlations between participation in uniform bodies programs and revision hours (r = 0.256) and also with and social hours (r = 0.147) but there was negative correlation between time spent in uniform body programs and GPA (r=-0.140). There were differences in the soft skills that student’s achieved from different uniform bodies programs. CONCLUSION: In conclusion, we found that students learnt and obtained various soft skills when they participated in uniform bodies programs. This will be useful for their later development especially when they are seeking employment upon graduation.